Analysis of the Evaluation Results of Deep Learning Training for Elementary School Teachers in Pekanbaru City Using the Kirkpatrick Level 1 and Level 2 Model - Kartika Ambarrhani; Maya Novita Sari (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
This study evaluates the effectiveness of the Deep Learning training program for elementary school teachers in Pekanbaru City using the Kirkpatrick Evaluation Model, specifically Level 1 (Reaction) and Level 2 (Learning). Using a descriptive-evaluative qualitative approach, data were collected through in-depth interviews, classroom observations, and document analysis with 16 teachers from 8 elementary schools. School principals, facilitators, and staff members from the Balai Guru dan Tenaga Kependidikan Provinsi Riau served as supporting informants to strengthen data triangulation. At Level 1, all dimensions of participants' reactions were categorized as good to very good, with the highest levels of satisfaction associated with facilitator competence and participant motivation. At Level 2, participants demonstrated a significant improvement in their understanding of the philosophies of mindful, meaningful, and joyful learning, as well as the four holistic dimensions. Nevertheless, the competencies of Critical Thinking and Creativity within the 6C framework remained susceptible to oversimplified interpretation. Overall, classroom observations revealed a measurable shift from a transmissive to a more facilitative approach to teaching and learning.